1978
DOI: 10.1180/claymin.1978.013.1.02
|View full text |Cite
|
Sign up to set email alerts
|

The 14 Å phase developed in heated dickites

Abstract: Dickites with well-ordered crystal structures and with relatively high dehydroxylation temperatures develop a 14 A phase when heated to temperatures in the range 550-800~ The actual spacing is close to 13-7-13"8 A. Dickites with less well-ordered structures and with lower dehydration temperatures give less development of this phase or none at all. Other kaolinite group minerals do not produce a similar phase. Thermal weightchange and differential thermal analysis data show that the 14 A phase develops to a max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Some samples exhibit a nearly symmetrical and relatively sharp peak (Mackenzie, 1957;Brindley and Porter, 1978), but most, including those in the present study, exhibit a broad asymmetric peak, often with a sub-endothermic peak at near midway between --450~ and the maximum. Brindley and Porter (1978) reviewed the DTA curves of Jamaican dickite and concluded that structurally well-ordered dickite generally gave a sharp endothermic peak near 700~ and generated a 14 ,~ d-spacing phase when dehydroxylation occurred (Brindley and Wan, 1978). Disordered dickite gives mainly a broad DTA endothermic peak.…”
Section: Chen Wang and Yangmentioning
confidence: 99%
“…Some samples exhibit a nearly symmetrical and relatively sharp peak (Mackenzie, 1957;Brindley and Porter, 1978), but most, including those in the present study, exhibit a broad asymmetric peak, often with a sub-endothermic peak at near midway between --450~ and the maximum. Brindley and Porter (1978) reviewed the DTA curves of Jamaican dickite and concluded that structurally well-ordered dickite generally gave a sharp endothermic peak near 700~ and generated a 14 ,~ d-spacing phase when dehydroxylation occurred (Brindley and Wan, 1978). Disordered dickite gives mainly a broad DTA endothermic peak.…”
Section: Chen Wang and Yangmentioning
confidence: 99%
“…It should be noted that the majority of studies have concentrated on the dehydroxylation of kaolinite. Dickite has received little attention (Roy and Brindley 1956;Brindley and Porter 1978;Brindley and Wan 1978;) and hence no definitive mechanism for the dehydroxylation of dickite has been forthcoming. Differential thermal analysis results would suggest that the dehydroxylation of dickite is different to that of kaolinite (Holdridge and Vaughan 1957).…”
Section: Oh ~-~ H + + 02-and H + +Oh-~-~ H20mentioning
confidence: 99%
“…Hill (1955) has reported the development of a 14/~-phase dickite on dehydroxylation. Brindley and Wan (1978) found that structurally well-ordered dickites give maximum development of a 14 ]k phase on heating, but that less well-ordered dickites show little or no development of this phase. The 14/k phase appeared for our dickite sample at 550~ and remained up to 800~…”
Section: Mineralogy Of Clays In the H-type Alteration Aureolementioning
confidence: 99%